An end to end key establishment scheme for detecting black hole attacks in mobile ad hoc networks - Baban Ahmed Mahmood; Aso Ahmed Majeed; Ahmed Chalak Shakir (Institute of Advanced Engineering and Science, 2021)
The wireless technology is in consistent and rapid development in this century such that it produces fast data rate and strong connectivity. Mobile ad hoc network (MANET) is an independent network wherein nodes function as both host and router. Routing protocols in MANET are prone to different attacks. Malicious nodes usually interfere the process of establishing routes and make it hard to build a valid route. In the literature, different mechanisms proposed to prohibit black hole attacks in which an adversary node blindly drops data packets. In this paper, a study is fulfilled of the advantages and disadvantages of some of the protocols presented in the literature and a novel method proposed that detects black hole attacks. A thorough, precise, and theoretical analysis is presented to show how the proposed method can prevent malicious nodes from impersonating benign nodes. A theoretical compareison conducted between the proposed method and some of the other methods presented in the literature. The comparison shows that the attacks exist on these protocols are detected and prevented by the proposed protocol.